2017
DOI: 10.1007/s00438-017-1313-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the duplicated intracellular lipid-binding protein genes of teleost fishes

Abstract: Increasing organismal complexity during the evolution of life has been attributed to the duplication of genes and entire genomes. More recently, theoretical models have been proposed that postulate the fate of duplicated genes, among them the duplication-degeneration-complementation (DDC) model. In the DDC model, the common fate of a duplicated gene is lost from the genome owing to nonfunctionalization. Duplicated genes are retained in the genome either by subfunctionalization, where the functions of the ances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 118 publications
8
29
0
Order By: Relevance
“…Together with the conserved FABP gene synteny analysis, we confirmed that the current FABP family gene/protein set might have resulted from multiple rounds of duplications and splicing editing divergence during evolution. These results regarding FABP evolution are consistent with the reports of Schaap [25] and M. Wright [35].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Together with the conserved FABP gene synteny analysis, we confirmed that the current FABP family gene/protein set might have resulted from multiple rounds of duplications and splicing editing divergence during evolution. These results regarding FABP evolution are consistent with the reports of Schaap [25] and M. Wright [35].…”
Section: Resultssupporting
confidence: 93%
“…Conserved synteny (the colocalization of genes on chromosomes) is sometimes used to describe the preservation of the precise order of genes on a chromosome passed down from a common ancestor [32], although many geneticists reject this use of the term [33]. Many studies have indicated that all FABPs are likely to have arisen from common ancestral genes through duplication and diversification [25,34,35]. Thus, we analyzed the synteny of FABP family genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This FABP diversity likely arose from the two successive rounds of whole genome duplication (WGD) that occurred in early vertebrates [53,54]. In contrast, FABP9 and FABP12 appear restricted to mammals [55], but FABP10 has been proposed in avian and teleost [56], revealing the relevance of FABP gene degeneration or duplication in the divergence of these chicken FABP genes from those of other vertebrates [23,53]. A previous study suggested FABP10 originated before the most recent common ancestor (MRCA) of tetrapod and bony fish [23].…”
Section: Discussionmentioning
confidence: 99%